Integrating analytical thinking skills into physical education to improve student learning outcomes - Jusuf Blegur; Yusi Riksa Yustiana; Agus Taufik; Muhamad Ilham; Sefri Hardiansyah (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
In the education curriculum in Indonesia, physical education is a medium for developing the potential of student learning outcomes in a comprehensive (cognitive, affective, and psychomotor) and sustainable manner. However, at the same time, teachers have not maximized analytical thinking supplements in learning and mastering student movements to optimize their physical education learning outcomes. This research used quantitative methods to examine the effect of analytical thinking skills on student learning outcomes. The participants were 24 elementary school students (mean age = 10.17+0.38) who were determined using a purposive sampling technique. Data on thinking skills were collected using instruments and rubrics for assessing analytical thinking skills. While the learning outcomes data use the final value of physical education learning. Data analysis used descriptive statistics and simple linear regression analysis. Descriptive analysis showed that students' analytical thinking skills were moderate (58.34%), and learning outcomes were good (100%). There is a significant influence between analytical thinking skills on student learning outcomes (t = 2.312, α = 0.031) with a determination value of 19.6%. Considering the essence of analytical thinking skills for learning outcomes and supporting students' life skills, the orientation of physical education learning outcomes parameters and the comprehensive and sustainable integration of analytical thinking into students' physical activities must be discussed further.